Policy analysis and decision making by the Governor of NTT regarding school entry hours - Abdul Canter Sangaji; Ulfatul Khoiriyah (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
The policy on school hours is a controversial policy, where the public tends to view the policy negatively. Amid the negative response from the public, researchers have balanced assumptions to look more deeply at the positive aspects of the decision-making made by the Governor of NTT, Victor Bungtilu Laiskodat, regarding the change in school entry hours in NTT. Therefore, based on these objectives, this research needs to be carried out as a reference in analyzing and describing the policy process and decision-making approach used by a policy actor so that later he can avoid himself fromfailure in decision making.This study uses qualitative research by collecting data using literature studies both reading books and information circulating from national and local media. The object of research is also limited to decision-making actors, Governor of NTT, Viktor Laiskodat, and supporters of this policy, the Office of Education in NTT. The results of the research show that Governor Victor as a policy actor in establishing this new policy can be categorized in the science of decision making as Doing First or doing first. This is because in Indonesia it is still not customary to advance school entry hours at 05.30 WITA. The move made by Governor Victor is something that is considered new in the world of education, causing a new polemic in the public space.